Experience with ospemifene in patients with vulvar and vaginal atrophy and urinary incontinence: case studies - Zuramis Estrada Blanco; Mariella Lilue; Santiago Palacios (BioExcel Publishing Ltd, 2020)
Pelvic floor muscle atrophy and collagen loss in connective tissue due to declining estrogen production in women as they age may underlie the increasing prevalence of urge and stress incontinence. Estrogen therapy can correct the deficiency of estrogen receptors in genitourinary structures after menopause, but estrogen is not suitable for all women. A series of retrospective studies showed that urinary symptoms improved in women with overactive bladder syndrome who were receiving ospemifene for vulvovaginal atrophy (VVA), a component of genitourinary syndrome of menopause. Two case studies presented in this article support the findings. The woman in case 1 was 76 years old, had a 4-year history of urinary incontinence (UI), and several risk factors for urinary symptoms. During 15 months' treatment with ospemifene for VVA, her urinary symptoms also improved as evidenced by a reduction (from four/day to one/day) in sanitary pad requirements to manage leakage. The patient in case 2 had predominantly moderate-to-severe VVA and mild mixed UI. During 6 months' treatment with ospemifene, she experienced marked improvement in VVA symptoms, including normalization of vaginal pH and disappearance of dyspareunia, accompanied by a decrease in urinary symptoms, which allowed her to resume a normal exercise program.